Analysis of Land Ownership Transfer to a Legal Entity Based on Tanah Grogot Court Decision No. 26/Pdt.G/2022/PN Tgt - Azizah, Shafiyah Nur (Semarang State University Undergraduate Law and Society Review, 2025)
This study examines the implementation of land ownership transfer to a legal entity based on the Decision of the Tanah Grogot District Court Number 26/Pdt.G/2022/PN Tgt. The research focuses on the gap between the legal authority of the court ruling and its practical implementation. The research method uses an empirical juridical approach with data collection techniques including interviews, observations, and documentation. The findings reveal that the cooperative, as the plaintiff, faced both administrative and social obstacles such as the absence of authentic deeds, uncooperative defendants, weak interagency coordination, and technical issues at the Land Office. Although the court decision has permanent legal force, the land transfer process cannot proceed due to unfulfilled administrative requirements. As a solution, the cooperative filed for real execution and used the court ruling as a legal basis to apply for Building Use Rights (HGB) or Usage Rights (HP) over the land. This study recommends strengthening institutional coordination, imposing sanctions on non-compliant parties, and digitizing land records. Thus, the implementation of court rulings in land disputes can effectively ensure legal certainty and protection for legal entities.